An Economic Approach to the Analysis of the Human Factor Substrate and the Measurement of the Risks that Form - I. S. Bogatyrev; A. N. Tsatsulin (Управленческое консультирование)
The article considers the problem of measuring risks and threats created by nature and characteristics of the human factor and affecting the efficiency and safety of activities at the micro level of the economy, in particular, in the environment of scientific and design organizations during the development of restoration projects at immovable cultural heritage sites located in St. Petersburg and the Leningrad Region. A literature review of sources covering the problem under study is conducted. The goal of the study is formulated, consisting in attempts to measure the impact of human factor risks on the efficiency of scientific and design work, and the tasks are outlined, the solution of which will allow achieving the goal. The object of the subject study is the assessment of complex damage and indirect losses, and the subject is defined as the procedures for measuring the effects of these risks. The methods and tools of the planned study are defined. A number of intermediate author’s results are obtained, clarifying the nature of the human factor, the conceptual apparatus of the topic, the classification of risks, threats and dangers that can cause significant damage to an economic entity, harm to its market activity, damage to its business reputation and brand value. Partial results were discussed, several stage conclusions were made. Directions for further joint research of the authors of the article were outlined, which can be considered the starting point and the beginning of the path in the systematic study of the problem of threat metrics from the human factor